Phenomenon of prostitution – between necessity and taboo? - Drapalska-Grochowicz, Marlena (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
Prostitution is a phenomenon that evokes extreme emotions in the discourse. Stereotypes and myths in which the phenomenon of prostitution has outgrown dwarf the real picture of this phenomenon. Nowadays, the most important issue is a reflection on causes and consequences of this phenomenon. The phenomenon of prostitution puts to the test traditional concepts defining human sexuality – what its limits are and how to separate what falls within socially acceptable norms and what does not. Prostitution, on the one hand, appears as a necessity and on the other hand as a safety valve for the society. The ambiguity of the phenomenon of prostitution is illustrated by doubts around the legalisation on prostitution.